Architecture of Mate Choice Decisions in Enchenopa Treehoppers - (:unkn) unknown (My University, 2022)
Mate selection is one of the most important choices a female can make for herself and her offspring. Variation in mate choice decisions has consequences for the maintenance of and the diversity within a population and the promotion of divergence between populations. Mate choice decisions arise from the interaction of two main components: “mate preferences” (the relative attractiveness of a potential mate) and “choosiness” (the effort put into procuring a preferred mate). My dissertation analyzes the relationship between the components involved in female mate choice decisions in Enchenopa binotata treehoppers. I take a three-pronged approach. First, I investigated how E. binotata females process a male mating signal with multiple elements. I tested the hypothesis of basic combinatorial processing against two competing hypotheses: beginning rule and no-ordering rule. This was done by presenting females with different arrangements of signal elements and recording the female responses. I found support for combinatorial processing, meaning that female treehoppers use rules for acceptable element combinations, which allows them to process complex signals when selecting mates. Second, I investigated how mate preferences and choosiness adaptively change over the lifetime of a female. Mate preference functions are described using 4 traits: tolerance, strength, responsiveness, and peak. Hypotheses were tested for all four preference function traits along with choosiness using vibrational playback experiments. All showed significant changes that allowed females to expand the pool of preferred mate types to procure a mating from the diminishing pool of available males. Females also increased their choosiness putting more effort into securing a preferred mate. Third, I looked at variation in mate choice decisions; testing whether individual female differences or the social context of what options are available contribute more to mate selection. We found considerable individual differences in preferred mate types, but found that our manipulation of the immediate social context had no effect. My dissertation deepens the breadth of knowledge about how mate choice decisions are made, which in turn helps us understand the consequences of variation in such decisions for the maintenance of population diversity and the promotion of speciation.
Keywords: Choosiness; Combinatorial Processing; Enchenopa binotata; Mate Choice; Mate Preferences; Sexual Selection